Removal of ciprofloxacin from aqueous solutions using pillared clays - Roca Jalil, María Eugenia (2017)
Emerging contaminants in the environment have caused enormous concern in the last few decades, and among them, antibiotics have received special attention. On the other hand, adsorption has shown to be a useful, low-cost, and eco-friendly method for the removal of this type of contaminants from water. This work is focused on the study of ciprofloxacin (CPX) removal from water by adsorption on pillared clays (PILC) under basic pH conditions, where CPX is in its anionic form (CPX-). Four different materials were synthetized, characterized, and studied as adsorbents of CPX (Al-, Fe-, Si-, and Zr-PILC). The highest CPX adsorption capacities of 100.6 and 122.1 mg g-1 were obtained for the Si- and Fe-PILC (respectively), and can be related to the porous structure of the PILCs. The suggested adsorption mechanism involves inner-sphere complexes formation as well as van der Waals interactions between CPX- and the available adsorption sites on the PILC surfaces.